2020
DOI: 10.36660/abc.20190349
|View full text |Cite
|
Sign up to set email alerts
|

Dieta Intermitente Atenua a Remodelação Cardíaca Causada pelo Exercício Físico

Abstract: Background: The effects of non-pharmacological interventions such as calorie restriction and exercise training on health and prevention of cardiovascular diseases have been investigated in clinical and experimental studies. Objective: To analyze the influence of intermittent fasting and exercise training on functional fitness, glycemia and cardiac remodeling. Methods: Wistar rats (n=60) were randomly divided into four groups: control, exercise training (ET), intermittent fasting (IF) and exercise training plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…Noteworthy, ample experimental evidence has indicated that the combination of exercise and IF lead to a greater improvement of metabolic parameters ( Figure 2 and Table 1 ). The interaction between IF and exercise may have potentiated the hormonal effects of insulin metabolism and is associated with higher glycemic tolerance, which is attributed to the increase in AMPK activity and GLUT4 protein [ 71 ]. In a 3-month randomized parallel-arm trial, the results demonstrated that ADF combined with aerobic exercise was effective for reducing intrahepatic triglycerides in adults with obesity and NAFLD [ 72 ].…”
Section: Modulation Effects Of Combining If and Physical Exercise On ...mentioning
confidence: 99%
“…Noteworthy, ample experimental evidence has indicated that the combination of exercise and IF lead to a greater improvement of metabolic parameters ( Figure 2 and Table 1 ). The interaction between IF and exercise may have potentiated the hormonal effects of insulin metabolism and is associated with higher glycemic tolerance, which is attributed to the increase in AMPK activity and GLUT4 protein [ 71 ]. In a 3-month randomized parallel-arm trial, the results demonstrated that ADF combined with aerobic exercise was effective for reducing intrahepatic triglycerides in adults with obesity and NAFLD [ 72 ].…”
Section: Modulation Effects Of Combining If and Physical Exercise On ...mentioning
confidence: 99%
“…After that, muscle samples were immediately frozen in liquid nitrogen and stored at −80 • C until analysis. The right tibia was dissected, measured using a pachymeter, and used to normalize muscle mass [41,42].…”
Section: General Characteristics Tissue Collection and Serum Biochemi...mentioning
confidence: 99%
“…Protein levels were analyzed by Western blot according to previous studies [41][42][43][44]. Protein was extracted using a RIPA buffer (1 mL/100 mg tissue) containing protease and phosphatase inhibitors.…”
Section: Western Blottingmentioning
confidence: 99%
“…As taxas de mortalidade padronizadas por idade para DCV atribuíveis a fatores de risco em 2018, no Brasil, para mulheres e homens, classificam os riscos dietéticos no segundo lugar do ranking , atrás apenas da hipertensão arterial. 9 Basilio et al 10 estudaram a influência da combinação da dieta intermitente (com restrição calórica) e exercício físico sobre a capacidade funcional, o metabolismo glicêmico e a remodelação cardíaca em ratos Wistar machos, durante 12 semanas. Sua hipótese era que o exercício físico ampliaria o desempenho físico e atenuaria a remodelação miocárdica decorrente da restrição calórica intermitente.…”
Section: Prevenção E Risco Cardiovascularunclassified
“…Estudo comparativo da doença coronariana microvascular causada por doença de Chagas com outras etiologias http://abccardiol.org/wp‐content/uploads/articles_xml/0066‐782X‐abc‐115‐06‐1094/0066‐782X‐abc‐115‐06‐1094.x64000.pdf Stefan 32 7. Quantificação de dano em DNA em diferentes tecidos em ratos com insuficiência cardíaca http://abccardiol.org/wp‐content/uploads/articles_xml/0066‐782X‐abc‐S0066‐782X2020000200234/0066‐782X‐abc‐S0066‐782X2020000200234‐pt.x64000.pdf Basilio 10 8. Dieta intermitente atenua a remodelação cardíaca causada pelo exercício físico http://abccardiol.org/wp‐content/uploads/articles_xml/0066‐782X‐abc‐115‐02‐0184/0066‐782X‐abc‐115‐02‐0184.x64000.pdf Santos 12 9.…”
Section: Introductionunclassified